Perencanaan Pondasi Bore Pile Menggunakan Metode Standard Penetration Test (SPT) Cone Penetration Test (CPT) dan Analisis Efisiensi Biaya (Studi Kasus Proyek Hotel Solis Ubud Resort and Spa) - Meidudga, Roberth Evander; Wismantara, I Gusti Ngurah Nyoman (Universitas Pendidikan Nasional, 2020)
The planned foundation at the hotel solis ubud resort and spa is a drill pole,caused soil conditions is impossible, to install shallow types. known from the results of soil tests obtained on the project, by using CPT method and SPT method. In this Thesis , the authors plan footing of the drill post by calculating capacity of the soil at that location with the planned depth using the data obtained from the building project, with two method, first standard penetrationt test (SPT) second cone penetration test (CPT) to compare cost efficiency of both methods in bore pile footing design, in hotel solis ubud resort and spa building project. the theoretical results obtained can be concluded that the SPT method used in the project, much more efficient in financing, than the results of the SPT method. on the calculation result get foundation size D = 45 cm for planning use method, whereas for planning using CPT method obtained size of foundation size D = 50 cm, with the same depth of 15m and the number of the same post that is 76 post.